Innovative Civic Education Practices with Vulnerable Children and Young People in Rural Areas: A Case Study - Celiešienė, Eglė; Bakšytė, Lina (Social Education / Socialinis ugdymas, 2023)
This article aims to present the practice of an innovative civic education project, adapting the integrated learning methodology “Project Citizen” to work with children and young people from vulnerable groups in rural areas. Using a participatory action research strategy, in-depth interviews were carried out with youth workers working in a youth centre (1), a day-care centre (3) and an open youth space (1) in four different rural settlements, who were implementing local projects. The results showed that the interpretation of citizenship in the education of children and young people from more vulnerable backgrounds should be contextualised in specific situations and integrated with individual needs, aspirations and capacities. The results provide insights into how to develop citizenship education when working with children and young people from vulnerable groups in smaller settlements.